Argumentação de estudantes da EJA - Ensino Médio no processo de aprendizagem de matemática - Sá, Eloar Barreto Feitoza (2021)
In this study, we focus the argument in mathematics. The ability to argue tends to be associated with the development of criticality, since it can favor reflective thinking, the production of knowledge and, therefore, the learning process (LEITÃO, 2011). Considering it as the expression of reasoning, it has a relevant relationship with mathematical skills to be developed in the school environment. In Mathematics Education, „reasoning‟, „representing‟, „arguing‟ and „communicating‟ are linked to competencies and skills considered fundamental to student learning and development, as evidenced by the Common National Curricular Base (Base Nacional Curricular Comum-BNCC). These capacities are articulated through the production of justifications, by students, for results achieved during the resolution of certain problems (BRASIL, 2017). In this context, our aim with the present study is to examine aspects of arguments issued by students of the Youth and Adult Education - High School (Educação de Jovens e Adultos - Ensino Médio - EJAEM) teaching method in answers that contain mathematical questions. It is a research with a qualitative approach, whose nature corresponds to a case study. Its realization occurred in four moments. In the first, we made observations of some of the remote classes of the Mathematics teacher from six school classes at the level of education of the study focus. Before that, we interviewed the referred teachers in search of information about their teaching trajectory, their lesson plans, the teaching of the discipline and their knowledge of argumentation. In a second step, we collected data for the characterization of the students participating, as well as their relationship with mathematics, from the application of a questionnaire. The third and fourth moments correspond, respectively, to the individual application of a list of questions involving mathematics in order to enable the issue of arguments and a group discussion to collectively reach solutions to other questions with mathematics. We examined the responses obtained with the individual lists and tried to classify the justifications, whenever possible, based on the types of evidence by Balacheff (1988). For the answers and justifications elaborated by the students collectively, we adopted the Toulmin model (2001) trying to identify the constituent elements of the constructed arguments. As a result, we noticed a weakness in the student's elaboration of arguments on issues involving mathematics, especially when those arguments are produced individually through writing. Thus, a significant number of responses submitted in writing did not have enough information to allow us to classify the types of evidence. In the case of the arguments produced from a communication in pairs, we found the predominance of justifications consisting of a description of the reasoning adopted by one of the components of each pair.